In Vivo Activation of a Mutant μ-Opioid Receptor by Naltrexone Produces a Potent Analgesic Effect But No Tolerance: Role of μ-Receptor Activation and δ-Receptor Blockade in Morphine Tolerance - Roy, Sabita (J Neurosci, 2005)
Opioid analgesics are the standard therapeutic agents for the treatment of pain, but their prolonged use is limited because of the development of tolerance and dependence. Recently, we reported the development of a μ-opioid receptor knock-in (KI) mouse in which the μ-opioid receptor was replaced by a mutant receptor (S196A) using a homologous recombination gene-targeting strategy. In these animals, the opioid antagonist naltrexone elicited antinociceptive effects similar to those of partial agonists acting in wild-type (WT) mice; however, development of tolerance and physical dependence were greatly reduced. In this study, we test the hypothesis that the failure of naltrexone to produce tolerance in these KI mice is attributable to its simultaneous inhibition of δ-opioid receptors and activation of μ-opioid receptors. Simultaneous implantation of a morphine pellet and continuous infusion of the δ-opioid receptor antagonist naltrindole prevented tolerance development to morphine in both WT and KI animals. Moreover, administration of SNC-80 [(+)-4-[(αR)-α-((2S,5R)-4-allyl-2,5-dimethyl-1-piperazinyl)-3-methoxybenzyl]-N,N-diethylbenzamide], a δ agonist, in the naltrexone-pelleted KI animals resulted in a dose-dependent induction in tolerance development to both morphine- and naltrexone-induced analgesia. We conclude that although simultaneous activation of both μ- and δ-opioid receptors results in tolerance development, μ-opioid receptor activation in conjunction with δ-opioid receptor blockade significantly attenuates the development of tolerance.